2018
DOI: 10.1155/2018/2373868
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil to Lymphocyte Ratio as a Predictor of Poor Prognosis in Metastatic Pancreatic Cancer Patients Treated with Nab-Paclitaxel plus Gemcitabine: A Propensity Score Analysis

Abstract: Background High neutrophil to lymphocyte ratio (NLR) has shown to be a predictor of poor outcomes in various malignancies, including pancreatic cancer. Methods We assessed 70 consecutive pts with histologically confirmed mPC who received chemotherapy with nab-paclitaxel/gemcitabine at two different European oncologic centers between January 2012 and November 2015. Variables assessed for prognostic correlations included age ≥ 66, sex, Karnofsky PS score, primary tumor site, baseline CA19.9 level ≥ 59xULN, 12-we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…In line with the GS model, the current study helped identify performance status, tumor stage, albumin, and NLR as independent prognostic factors that predict survival outcome. Several prognostic models have been developed for survival prediction among APC patients receiving first‐line palliative chemotherapy . Apart from patient factors (age, sex, performance status, weight loss), laboratory variables (albumin, white cell count, NLR, tumor markers) and tumor characteristics (stage, tumor size, metastatic organ, ascites) have all been reported to be independent prognosticators in different prognostic models .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In line with the GS model, the current study helped identify performance status, tumor stage, albumin, and NLR as independent prognostic factors that predict survival outcome. Several prognostic models have been developed for survival prediction among APC patients receiving first‐line palliative chemotherapy . Apart from patient factors (age, sex, performance status, weight loss), laboratory variables (albumin, white cell count, NLR, tumor markers) and tumor characteristics (stage, tumor size, metastatic organ, ascites) have all been reported to be independent prognosticators in different prognostic models .…”
Section: Discussionmentioning
confidence: 99%
“…Table summarizes and compares 13 published prognostic models for the prediction of the survival outcome of PC patients receiving palliative chemotherapy from a literature review . Only one of the models was designed prospectively ; the others were retrospective studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An increasing number of studies have demonstrated that the inflammatory response plays a key role in the changes to the microenvironment of normal tissue, and thus is an important factor for tumor occurrence and development. [ 5 , 6 ] Several biomarkers have been identified as prognostic risk factors for various types of cancer, including interleukin-6 (IL-6) in ovarian cancer, [ 7 ] C-reactive protein (CRP) in hepatocellular carcinoma, [ 8 ] CRP and albumin (ALB) ratio in cervical cancer, [ 9 ] aspartate aminotransferase (AST) and the neutrophil ratio in intrahepatic cholangiocarcinoma, [ 10 ] and the platelet-to-lymphocyte ratio (PLR) in breast cancer. [ 11 ] The present study aimed to investigate the potential correlation between the NLR and the prognosis of DCC patients after radical surgery.…”
Section: Introductionmentioning
confidence: 99%